2015
DOI: 10.1016/j.apjtb.2015.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing α-synuclein aggregation by methanolic extract of Centella asiatica in zebrafish Parkinson's model

Abstract: Objective: To observe the effects of Centella asiatica (C. asiatica) methanolic extract on a-synuclein aggregation and its expression in rotenone-exposed zebrafish. Methods: Zebrafish (Danio rerio) were exposed to 5 mg/L rotenone for 28 days and coincubated with 2.5, 5.0 and 10.0 mg/mL of C. asiatica methanolic extract. The medium was changed every 48 h for maintain the concentration of rotenone and extract. After 28 days zebrafish were sacrificed on the ice block and protein was isolated from zebrafish brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 47 publications
0
23
0
3
Order By: Relevance
“…Data on many recent experimental studies have scientifically validated the traditional uses of the extract of Mandukaparni. These findings endorse that the plant having multiple therapeutic potentials, which were amply and vividly demonstrated by different animal models such as wound-healing model in rat, [10][11] streptozocin-induced Alzheimeir's model 12 , zebrafish Parkinson's model, 13 adriamycin-induced cardiomyopathy model, 14 nitroglycerine and bradykinin induced hyperalgesia (migraine) model, 15 radiationinduced dermatitis model, memory impairment induced by cerebral ischemia-reperfusion 16 and also having anxiolytic, 17 neuronal dendritic growth and nerve stimulating effects, 18 suppression of scars in diabetic patients, 19 and reverse mutation assay for non-toxicity, safety and nonmutagenicity of the extract, 20 protection of healthy cells against radiationinduced damages. 21 However, the botanical standards specified for evaluation of intact plant material of Centella asiatica in literature [22][23][24][25] seemed to be too scanty and not exhaustive enough to extricate the crude raw materials from the adulterants and substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…Data on many recent experimental studies have scientifically validated the traditional uses of the extract of Mandukaparni. These findings endorse that the plant having multiple therapeutic potentials, which were amply and vividly demonstrated by different animal models such as wound-healing model in rat, [10][11] streptozocin-induced Alzheimeir's model 12 , zebrafish Parkinson's model, 13 adriamycin-induced cardiomyopathy model, 14 nitroglycerine and bradykinin induced hyperalgesia (migraine) model, 15 radiationinduced dermatitis model, memory impairment induced by cerebral ischemia-reperfusion 16 and also having anxiolytic, 17 neuronal dendritic growth and nerve stimulating effects, 18 suppression of scars in diabetic patients, 19 and reverse mutation assay for non-toxicity, safety and nonmutagenicity of the extract, 20 protection of healthy cells against radiationinduced damages. 21 However, the botanical standards specified for evaluation of intact plant material of Centella asiatica in literature [22][23][24][25] seemed to be too scanty and not exhaustive enough to extricate the crude raw materials from the adulterants and substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the study conducted by showing the increased α-synuclein aggregation up to 300% in zebrafish midbrain area exposed with rotenone and then connected to the decreased locomotor activity describing the clinical form of bradykinesia parkinsonism occurring in Parkinson disease. 34 α-synuclein expression in C. asiatica group showed the lowest result and it did not differ significantly with the control group, thus it can be concluded that the administration of C. asiatica extract is able to perform the decreased α-synuclein expression exposed with rotenone. This is in line with the previous study in which the administration of C. asiatica extract [5] and [10] μg/mL is able to decrease α-synuclein aggregation if given with rotenone.…”
Section: Discussion Locomotor Activitymentioning
confidence: 75%
“…28,29,30,31,32,33 C.asiatica extract with a concentration of 10 µg/L provides an increase in tyrosine hydroxylase (TH) which is a tyrosine catalyst enzyme into L-dihydroxyphenylalanine (L-dopa) which later turns to dopamine, accompanied by improved locomotor activity, as well as decreased αsynuclein expression in zebrafish Parkinson model. 34,35 Zebrafish is one of the Parkinson model animals which have the structure and function of organs including a dopaminergic system with genetic homology with mammals reaching 70 -80%. Besides, zebrafish has other advantages like easy maintenance, affordable, and fast breeding.…”
Section: Research Article Open Accessmentioning
confidence: 99%
“…The emerging use of the zebrafish model in neurological and neurodegenerative human diseases (such as PD, autism, Huntington's disease, and Alzheimer's disease) was described by Xi et al [ 12 ] and Brennan [ 13 ]. Despite that some disease phenotypes which are caused by orthologue genes can be very different, particularly when comparing fish and humans [ 14 ], it was shown that more than 70% of all human disease genes have functional homologs in Danio rerio [ 15 , 16 ]. In this way, the fast growing and easy-to-breed zebrafish could be a reasonable choice when contemplating to keep thousands of animals at low costs [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite that some disease phenotypes which are caused by orthologue genes can be very different, particularly when comparing fish and humans [ 14 ], it was shown that more than 70% of all human disease genes have functional homologs in Danio rerio [ 15 , 16 ]. In this way, the fast growing and easy-to-breed zebrafish could be a reasonable choice when contemplating to keep thousands of animals at low costs [ 16 , 17 ]. While zebrafish was originally considered as a bridge connection in the experimental gap between fly/worm and mouse/human in studying embryo development, it was shown that as the new research methodologies and genetic tools were updated, the zebrafish animal model was reported to be well suited to both developmental and genetic analysis [ 18 ] as well as complex human disorders [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%